Optical Coherence Tomography Angiography following Scleral Buckling Surgery - Sodhi, Punita Kumari; Sharma, Anu; Hasan, Nasiq (Nepalese Journal of Ophthalmology, 2021)
Introduction: The retinal changes following scleral buckling surgery (SBS) for rhegmatogenous retinal detachment (RRD) have been rarely evaluated with optical coherence tomography angiography (OCTA). Methods: A 40 years old male presented with subtotal RD involving the macula and had best corrected visual acuity of logmar 2.3 in the affected right eye. Five months after applying 120 degree scleral buckle, swept source optical coherence tomography (SSOCT) and swept source optical coherence tomography angiography (SS-OCTA) were done. Result: At five months post-surgery, despite a settled retina in the operated eye, the patient had vision of logmar 1 and thin retinal nerve fibre layer (115 micrometer). The SSOCT showed inner segment-outer segment (IS-OS) junction disruption, thinned retinal pigment epithelium, central macular thickness of 275 micrometer and subfoveal choroidal thickness of 222 micrometer. A 3x3 mm macular OCTA scan showed a normal foveal avascular zone along with higher values for vascular density in superficial capillary plexus in all quadrants except temporal quadrant in operated eye as compared to fellow eye. Conclusion: The SBS with 120 degree buckle did not lead to a reduced vascular density in superficial capillary plexus in the operated eye with respect to fellow eye.